(untitled) (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Ghofur A, Hadisaputro S, Sayono S. 2024. Detection of microfilaria L3 and insecticide resistance among wild-caught mosquito vectors in endemic areas of lymphatic filariasis. Biodiversitas 25: 1975-1983. The decline in the global prevalence of Lymphatic Filariasis (LF) is evident in the persistent endemic foci in Africa and Southeast Asia. In this context, the presence of infectious and insecticide-resistant mosquitoes and the annual biting rate in the area are key to microfilaria transmission. Therefore, this research aimed to determine insecticide resistance and microfilariae infection in mosquito vectors in endemic areas. In Jenggot and Medono Villages, twice entomological surveys were conducted based on six LF cases, where indoor and outdoor mosquito capturing was carried out in ten houses within a 100 m radius of each case as well as household interviews about insecticide use. In addition, laboratory works were performed for species identification and detection of ovarian dilatation, microfilariae infection, and knockdown resistance mutations. A total of 1,197 and 581 mosquitoes were distributed to five species and their proportions, namely Culex quinquefasciatus (69.59 and 65.40%), Cx. tritaeniorhynchus (5.76 and 0.00%), Cx. vishnui (5.85 and 27.54%), Anopheles vagus (0.58 and 0.00%), and Aedes aegypti (18.21 and 7.06%). The percentage of female mosquito infection, parity, and microfilaria were 66.25 and 86.00%, 63.37 and 70.95%, as well as 0.00 and 1.34%, respectively. Furthermore, TTA-TTT, TTA-CTA, and TTA-TGT base substitutions were reported in codon 1014 of Cx. quinquefasciatus VGSC gene with proportions of 81.66, 1.67, and 26.67%, respectively. The result showed that the vulnerability of the research location to transmission emphasized the necessity for early detection, vector control, and further analyses of the susceptibility of microfilariae to antiparasitic drugs.